Circulating tumor cells in gastrointestinal malignancies - Weiss, Guy A.; Samuel, Sandeep T.; Ustwani, Omar Al; Iancu, Dan (Translational Gastrointestinal Cancer; Vol 2, No 3 (July 06, 2013): Translational Gastrointestinal Cancer, 2013)
Circulating tumor cells (CTCs) are involved in the metastatic process and have been detected in malignancies of epithelial origin. Several isolation techniques have been developed for the detection of CTC. Herein, we review the current literature regarding cytometric and nucleic acid based CTC detection in different stages of gastrointestinal cancers, including colorectal, pancreatic, hepatobiliary, esophageal, gastric, and small intestine malignancies, along with their potential role in prognosis and management.